A COMPARATIVE TYPOLOGY OF 15TH CENTURY ENGLISH AND UZBEK LITERATURE - Axmadova Shaxnoza Qilich qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article explores the literary landscape of the 15th century by conducting a comparative typology of English and Uzbek literature. Through a thorough examination of the cultural, social, and historical contexts, this study aims to highlight the similarities and differences between these two distinct literary traditions. The research employs a multidisciplinary approach, drawing on linguistic, historical, and literary analysis to unravel the intricacies of literary expression in both regions during the 15th century.